HUBUNGAN TINGKAT KECANDUAN BERMAIN ONLINE GAME DENGAN TINGKAT ASTENOPIA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA AMBON - Abdur Rahman Assagaf; Carmila L. Tamtelahitu; Halida Rahawarin (Fakultas Kedokteran Universitas Pattimura, 2020)
Online game, a kind of game that is accesed using internet network, enable the connection and interaction of many game players around the world. Long duration of online gaming may cause confusing illution with reality, lack of concentration, loss of body weight and visual disturbance. Decrease of visual function due to online gaming usually begins with eye strain (asthenopia) and dry eye. This study aimed to evaluate the association between online game addiction level and asthenopia level in students of Medical Faculty of Pattimura University Ambon. Cross sectional design with quantitative approach and questionnaire as instrument were used in this study. Univariate and bivariate analysis were done and the results showed that 66 (82.5%) respondents are addicted to online game, 14 (17.5%) respondents like to play online game. 64 (80.0%) respondents experienced mild asthenopia, 16 (20.0%) respondents experienced moderate asthenopia. All respondents experienced asthenopia and no respondents experienced severe asthenopia. Chi-square test results showed a p value of 0.139 which means that there is no association between online game addiction level with asthenopia level in students of Medical Faculty of Pattimura University Ambon.